Neoarchean UHT metamorphism and paleoproterozoic UHT reworking at Uweinat in the East Sahara Ghost Craton, SW Egypt: evidence from petrology and texturally controlled in situ monazite dating - Karmakar, Shreya; Schenk, Volker (Journal of petrology, 2015)
Abstract. The Uweinat-Kamil basement complex, in the central part of the East Sahara Ghost Craton (ESGC) in NE Africa, is the only inlier in the craton that co
Gesehen am 16.06.2020